Diversity of microbial, biocontrol agents and nematode abundance on a susceptible Prunus rootstock under a Meloidogyne root gradient infection - Clavero-Camacho, Ilenia; Ruiz-Cuenca, Alba N.; Cantalapiedra-Navarrete, Carolina; Castillo, Pablo; Palomares-Rius, Juan E. (Frontiers in Plant Science, 2024)
Root-knot nematodes (RKNs) of the genus Meloidogyne are one of the most damaging genera to cultivated woody plants with a worldwide distribution. The knowledge of the soil and rhizosphere microbiota of almonds infested with Meloidogyne could help to establish new sustainable and efficient management strategies. However, the soil microbiota interaction in deciduous woody plants infected with RKNs is scarcely studied. This research was carried out in six commercial almond groves located in southern Spain and infested with different levels of Meloidogyne spp. within each grove. Several parameters were measured: nematode assemblages, levels and biocontrol agents in Meloidogyne’s eggs, levels of specific biocontrol agents in rhizoplane and soil, levels of bacteria and fungi in rhizoplane and soil, fungal and bacterial communities by high-throughput sequencing of internal transcribed spacer (ITS), and 16S rRNA gene in soil and rhizosphere of the susceptible almond hybrid rootstock GF-677 infested with Meloidogyne spp. The studied almond groves showed soil degradation by nematode assemblies and fungi:bacterial ratio. Fungal parasites of Meloidogyne eggs were found in 56.25% of the samples. However, the percentage of parasitized eggs by fungi ranged from 1% to 8%. Three fungal species were isolated from Meloidogyne eggs, specifically Pochonia chlamydosporia, Purpureocillium lilacinum, and Trichoderma asperellum. The diversity and composition of the microbial communities were more affected by the sample type (soil vs rhizosphere) and by the geographical location of the samples than by the Meloidogyne density, which could be explained by the vigorous hybrid rootstock GF-677 and a possible dilution effect. However, the saprotrophic function in the functional guilds of the fungal ASV was increased in the highly infected roots vs the low infected roots. These results indicate that the presence of biocontrol agents in almond fields and the development of new management strategies could increase their populations to control partially RKN infection levels.